Desobediência . Disobedience - Azevedo, Licinio (Brazil, 2002)
Soros Documentary Fund “Disobedience” tells the story of a woman in Mozambique who is accused of having caused the suicide of her alcoholic husband by being disobedient and having a spirit-husband. As a result, the woman is persecuted and humiliated. Twice she manages to prove her innocence but even so, she is punished mercilessly. Based on a real story, the actual woman plays herself, the role of the husband is played by the deceased husband’s twin bother and the community that has shunned the real-life woman plays itself.